Assessing the Impact of Covid-19 on Workers of the Informal Sector: Evidence from Urban Slums in Dhaka North City Corporation, Bangladesh (Jagannath University Journal of Life and Earth Sciences, 2025)
The corona virus pandemic was an unavoidable situation worldwide. The study's objective is to determine the impacts of COVID-19 on the livelihood of informal workers and the associated challenges. The primary and secondary data regarding the livelihoods of informal workers were collected and analyzed using the Statistical Package for the Social Sciences (SPSS) 26.0.The primary data were collected through a semi-structured questionnaire and Focus Group Discussion (FGD). The study found that many COVID-19 cases among residents impact a wide range of incomes, especially for those with lower incomes. The research was conducted among workers in informal sectors and low-income individuals, including rickshaw pullers, hawkers, drivers, waste pickers, and housemates. Following the COVID-19 pandemic, maintaining social distancing and hygiene behaviors exacerbated the livelihoods of informal workers. Moreover, workers in the informal sector were affected in various ways, including disruptions to the food supply chain, health insecurity, and limited working opportunities due to movement restrictions during the lockdown. Therefore, people in informal sectors lost their purchasing power due to job losses and movement restrictions. The study helps policymakers and victims understand how to better prepare for the pandemic next time.Jagannath University Journal of Life and Earth Sciences, 10 (2): 125-142 (June 2024)